2015
DOI: 10.1111/jog.12697
|View full text |Cite
|
Sign up to set email alerts
|

Should magnesium sulfate be administered to women with mild pre‐eclampsia? A systematic review of published reports on eclampsia

Abstract: Although eclampsia is known to result from severe pre-eclampsia with or without organ function derangement, this review has revealed that a significant number of eclamptic women had either normal blood pressure or mild-to-moderate hypertension immediately before seizure. The findings are apparently in support of initiating magnesium sulfate prophylaxis to all women with mild pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 73 publications
2
36
0
10
Order By: Relevance
“…No existe una secuencia sintomática previa a la convulsión y podemos ver casos en los cuales la convulsión es la manifestación clínica inicial del daño cerebral. Un reciente metaanálisis encuentra 25% de casos (7% en nuestra serie) que debutan convulsionando (12) . La cefalea es el síntoma más asociado a la inminencia de eclampsia; nosotros la encontramos en 87,9% de los casos; otras series reportan 45 a 80% (12) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…No existe una secuencia sintomática previa a la convulsión y podemos ver casos en los cuales la convulsión es la manifestación clínica inicial del daño cerebral. Un reciente metaanálisis encuentra 25% de casos (7% en nuestra serie) que debutan convulsionando (12) . La cefalea es el síntoma más asociado a la inminencia de eclampsia; nosotros la encontramos en 87,9% de los casos; otras series reportan 45 a 80% (12) .…”
Section: Discussionunclassified
“…Un reciente metaanálisis encuentra 25% de casos (7% en nuestra serie) que debutan convulsionando (12) . La cefalea es el síntoma más asociado a la inminencia de eclampsia; nosotros la encontramos en 87,9% de los casos; otras series reportan 45 a 80% (12) . La alta asociación se explica dentro del contexto de la PRES por el edema cerebral como fenómeno fisiopatológico básico; este es producido por la alteración de la permeabilidad de la BHE en el contexto de la preeclampsia (17,18) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Indeed one study has reported that a significant number of eclamptic women had either normal blood pressure or mild-tomoderate hypertension immediately before seizure and the findings are apparently in support of initiating MgSO 4 prophylaxis to all women with mild pre-eclampsia [17]. But Baha et al represent that there are not acceptable benefit-to-risk ratio of administration of MgSO 4 for prophylaxis in mild preeclampsia and routine use is not recommended [18].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium sulphate has been widely used as a tocolytic agent and an anticonvulsant for the treatment of preterm labour and pre-eclampsia, respectively [15] [16]. The magnesium ion was initially discovered to be an N-methyl-D-aspartate glutamate (NMDA) receptor blocker, which can alter the perception and duration of pain in animal studies [17].…”
Section: Introductionmentioning
confidence: 99%